Comparison of risk factors and outcomes in HIV immune complex kidney disease and HIV-associated nephropathy - Foy, Matthew C; Estrella, Michelle M; Lucas, Gregory M; Tahir, Faryal; Fine, Derek M; Moore, Richard D; Atta, Mohamed G (Clinical journal of the American Society of Nephrology, 2013)
HIV-associated nephropathy (HIVAN) is well described, but the clinical features of a group of renal pathologies characterized by Ig or immune complex depositions referred to as HIV-associated immune complex kidney disease (HIVICK) have not been well established. The objective of this study is to assess risk factors for HIVICK compared with contemporaneous control participants. A nested case-control study of 751 HIV-infected patients followed from January 1996 to June 2010 was conducted. Groups were compared using the chi-squared test or rank-sum analysis. Conditional logistic regression was used to estimate odds ratios (ORs) for HIVICK. Incidences of overall ESRD and with/without combined antiretroviral therapy (cART) exposure were calculated. HIVICK patients were predominantly African American (92%). Compared with matched controls, patients with HIVICK were more likely to have HIV RNA >400 copies/ml (OR, 2.5; 95% confidence interval [95% CI], 1.2 to 5.2), diabetes (OR, 2.8; 95% CI, 1.1 to 6.8), and hypertension (OR, 2.3; 95% CI, 1.2 to 4.5). Compared with HIVAN, patients with HIVICK had more antiretroviral therapy exposure, lower HIV viral loads, and higher CD4 and estimated GFR. ESRD was less common in the HIVICK versus the HIVAN group (30% versus 82%; P<0.001), and the use of cART was not associated with ESRD in HIVICK patients (25% versus 26; P=0.39). HIVICK was predominantly observed in African-American patients and associated with advanced HIV disease. ESRD incidence is lower in HIVICK patients compared with those with HIVAN. Unlike HIVAN, cART use was not associated with the incidence of ESRD in HIVICK.